1999
DOI: 10.1177/001440299906500207
|View full text |Cite
|
Sign up to set email alerts
|

A National Perspective of Competencies for Teachers of Individuals with Physical and Health Disabilities

Abstract: With the growing trend towards generic certification, questions arise concerning the extent of knowledge and skills teachers have in instructing students with physical and health disabilities. This national study examines the knowledge and skills of teachers instructing students with physical and health disabilities, the perceptions of their special education directors, the resources available through their state Departments of Education, and the competencies included in physical and health disabilities at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Another proactive intervention may be providing additional training to special educators who are certified to teach students with physical and health disabilities. In a survey of these educators, 40% reported that they were not well trained in 11 of 23 critical competencies 31 . Although these school professionals have a generally positive attitude about children with chronic illness in their classrooms, they remain concerned with several real risks, most notably medical emergencies (53% of educators) and legal liability (27%) 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Another proactive intervention may be providing additional training to special educators who are certified to teach students with physical and health disabilities. In a survey of these educators, 40% reported that they were not well trained in 11 of 23 critical competencies 31 . Although these school professionals have a generally positive attitude about children with chronic illness in their classrooms, they remain concerned with several real risks, most notably medical emergencies (53% of educators) and legal liability (27%) 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Participants were practicing teachers who typically had one study day per week to work on the programme. The advantages of seeking the views of teachers about their preparation programmes in order to shed light on how programmes might be improved are highlighted in the literature and was the motivation for this study (Conderman et al 2013;Heller et al 1999;Lombardi and Hunka 2001). The aim of the overall research project, from which this article is drawn, was to investigate the perceptions of students who recently graduated about the importance of the competencies addressed in the programme to their professional work, and the extent to which they considered they had been enabled to develop those competencies, as well as to identify factors that acted as barriers or enablers to their learning within the programme.…”
Section: Specialist Teaching Programmementioning
confidence: 99%
“…Heller et al (1999) assessed the perceived competency of general education and special education teachers, who taught students with physical and health impairments, with respect to their preparation for working effectively with that population. Among special educators who were certified to teach students with physical and health disabilities, 40% reported that they were not well trained in 11 of 23 critical competencies.…”
Section: Exce_ntional Childrenmentioning
confidence: 99%
“…In part, the ability to plan for and respond appropriately to the 19 student's educational needs and health needs is contingent on the training received at the preservice level for future special and general educators. State Departments of Education must reexamine teacher-certification requirements to assure that those leaving teacher-preparation programs acquire the know ledge and skills necessary to teach students with physical and health disabilities (Heller et al, 1999).…”
Section: Summary and Recommendationsmentioning
confidence: 99%